Il diritto “sospeso”. La non-soluzione distopica de La notte del giudizio - Monceri, Francesco (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
This work aims to investigate the influence of cinema on the political/legal phenomenon, through the analysis of a specific cinematographic product (The Purge, James DeMonaco, 2013). In particular, it aims to show that the representation of dys-topian realities in cinematographic fiction – in many cases also through a transposition of re-readings of literary products – also constitutes an attempt to give an answer to extremely topical issues, with regard to which legal and political reflection encounters more and more obstacles to finding concrete forms of exercise. In fact, the analysis pro-posed by films has an obvious interest both as a forerunner of times and, with the same force, as a critical representation of reality. In the case of the film under consideration, we are dealing with the representation of certain legal mechanisms affecting fundamen-tal social rights and also the administrative law